2016
DOI: 10.2298/gensr1602729m
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of common bean accessions from former Yugoslav Republic of Macedonia as revealed by molecular and morphological markers

Abstract: Cultivation of common bean has a long tradition in the Former Yugoslav Republic of Macedonia (FYROM) and is still nowadays important part of the human diet. In a study reported here 71 accessions from the FYROM were assessed for genetic diversity with the aim to provide information on genetic structure of Macedonian common bean germplasm and to depict its peculiarities. A total of 71 accessions were assessed using 13 microsatellite and 16 morphological markers. The average number of alleles p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The length of the common bean stem fifth internode on the main stem measured in the fifteen genotypes showed some discrimination between the resistant, tolerant and susceptible genotypes. The measurements varied among all the genotypes and these results are in agreement with the studies made by Maras et al (2016) who reported the stem length of fifth internode on the main stem of common bean genotypes to be associated with disease incidence and severity cases. Environment x genotype interaction was not significant but the genotypes were highly significant at p ≤ 0.001.…”
Section: Length Of the Fifth Internodesupporting
confidence: 91%
See 1 more Smart Citation
“…The length of the common bean stem fifth internode on the main stem measured in the fifteen genotypes showed some discrimination between the resistant, tolerant and susceptible genotypes. The measurements varied among all the genotypes and these results are in agreement with the studies made by Maras et al (2016) who reported the stem length of fifth internode on the main stem of common bean genotypes to be associated with disease incidence and severity cases. Environment x genotype interaction was not significant but the genotypes were highly significant at p ≤ 0.001.…”
Section: Length Of the Fifth Internodesupporting
confidence: 91%
“…Visual observation made on the fifteen genotypes revealed broadly ovate leaflets with acuminate apices, the petial of the terminal leaflets were longer than those below. Past research made by Buah et al (2017) and Maras et al (2016) classified bracteole shape of plant leaves into; cordate, ovate, lanceolate and triangle. Therefore the recent research characterized the fifteen bean genotypes under field study as having one variable (100%), which was ovate leave shape and therefore there was no significance of leaf shapes in anthracnose resistance.…”
Section: Bracteolate Shape Classificationmentioning
confidence: 99%
“…Although the variability of common-bean accessions from central and South-Eastern Europe has already been reported in terms of morphological and molecular markers [35][36][37][38], such information on the runner bean from this region was lacking. Recently, runner-bean seeds of a Slovenian collection were characterised morphologically [14], although there remain few data for other traits, and none for runner beans from the other South-Eastern European countries covered here.…”
Section: Discussionmentioning
confidence: 99%
“…Morpho-agronomic information in this study will help to promote runner-bean breeding for the development of new varieties with favourable traits. To date, only limited information is available on runner-bean accessions from South-Eastern Europe [14,37,39], as compared to the common bean [14,[35][36][37][38]40]. As a further step, analysis of this diversity using molecular approaches is recommended, to provide more information on the overall genetic diversity, and potentially on the genes responsible for the specific morpho-agronomic traits in this runner-bean collection from South-Eastern Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation